Oxidative stress in bronchial asthma: A clinical study - Dutt HK, Gaur S, Kumar A, Goswami S (Journal of Applied Pharmaceutical Science)
Bronchial asthma is a chronic inflammatory disorder of airways. Recently, oxidative stress has been implicated in the pathogenesis of the disease. Several studies have documented the total antioxidant activity (AOA) of saliva and serum as a potential biomarker for redox state of body. The present study has been designed to assess the redox status of patients, by determining the total AOA of the serum and saliva and correlating it with the disease status. The study was carried out on two groups: control (normal) healthy volunteers) and asthmatic patients attending OPD of Department of Pulmonary Medicine. Severity of asthma was graded using Global Initiative for Asthma (GINA) 2010 guidelines. AOA was assayed spectrophotometrically by measuring the inhibitory potential of saliva and serum against in vitro production of thiobarbituric acid reactive substances (TBARS). After drug treatment, patients were followed for a period of three months and AOA was measured again in saliva and serum. AOA in serum was significantly higher than that in saliva in the control subjects. Asthmatic patients exhibited a decrease in both serum and salivary AOA as compared to control. The decrease in AOA in saliva was more pronounced than that observed in serum. Significantly, the decrease in serum and salivary AOA correlated well with the severity of disease process. AOA in serum and saliva is a good indicator for assessing the severity and progress of bronchial asthma.
Keywords: Bronchial asthma, Oxidative stress, AOA, GINA, TBARS.